Modified Percutaneous Kirschner Wire with Mutual Linking Technique in Proximal Humeral Fracture: A Technique Note and Preliminary Results - Hao-Ming Chang; Pei-Yuan Lee; Wei-Ren Su; Cheng-Li Lin (Formosan Journal of Musculoskeletal Disorders)
Background: Treating proximal humeral fracture (PHF) with percutaneous pinning is a relatively minimally invasive procedure, but complications including pin migration and loss of reduction have been reported. Objectives: We aimed to describe a novel modified percutaneous pinning with mutual linking technique (MPPMLT) for PHFs, which may decrease such complications. Materials and Methods: Six patients with PHFs received close reduction and MPPMLT. All wires were removed about 6 weeks postoperatively followed by progressive rehabilitation. We used the following radiograph to evaluate bony union, wire migration, and fragment displacement. Clinical outcomes were evaluated using range of motion of affected joint, Visual Analog Score (VAS), University of California at Los Angeles Shoulder Rating Score (UCLA), and the American Shoulder and Elbow Surgeons Shoulder Score (ASES). Results: All cases were followed up after an average of 12.6 months. The mean of anterior forward flexion of the injured shoulder was 166.7° at the final follow-up. The means of the VAS, UCLA score, and ASES were 0.3, 31.8, and 92.4, respectively. No wire migrations or fracture displacements were noted in our cases. There were also no deep infection, nonunion, implant failure, or avascular necrosis of the humeral head observed during the follow-ups. Conclusions: With this MPPMLT, minimally invasive approach could be achieved and additional stability was provided by mutually linking the wires to reduce pin migration and fracture displacement in PHFs.